PENGUKURAN PARAMETER KUALITAS UDARA (CO, NO2, SO2, O3 DAN PM10) DI BUKIT KOTOTABANG BERBASIS ISPU - Agusta Kurniawan (Jurnal Teknosains, 2017)
Bukit Kototabang, West Sumatera is one of the 34 global global (Global scale) monitoring stations in the world. Bukit Kototabang GAW Station is an implementation of the Global Atmosphere Watch (GAW) program initiated by the World Meteorological Organization (WMO) as an effort to monitor global atmospheric conditions. The Global Atmospheric Watch (GAW) Stations have duty to obtain atmospheric data and air quality data in remote area or relatively clean areas and far away from anthropogenic activity. Measurements of air quality parameters (CO, NO2, SO2, O3 and PM10) are continuously conducted at Bukit Kototabang. The monitoring data at Bukit Kototabang GAW Station in 2012 which is converted to Indonesian Air Pollution Standard Index shows the air quality is still good, shown by 353 days classified as clean (index = 0-50), 10 days is moderate (index = 51-100), and 1 day is very unhealthy (index = 200-299). That means 3% of daily air quality in Bukit Kototabang in 2012 is not good.